'Some records manager will take care of it' – Records management in the context of mobile work. (June 2013) - Mäkinen, Sari
Mobile work challenges organizational records management. This paper reports the results of a study in three case organizations on how the organizations' records management meets and adapts to the increasing role of mobile work. Data was collected by interviewing mobile workers and record management professionals. Documentary materials were used to analyse official records management policies. The findings revealed that documented organizational policies do not take into account mobile work, and cannot effectively support personal or corporate records management in mobile work. Records management professionals were poorly informed of the extent of mobile work in the organization, and of the special problems related to managing records in mobile work. The overall conclusion is that organizations should pay more attention to the new requirements for records management caused by mobile work.